ELECTRONIC MODULE BASED ON PROBLEM BASED LEARNING TO IMPROVE THE LIFE SKILLS OF GRADE V STUDENTS OF MADRASAH IBTIDAIYAH - Erfayliana, Yudesta; Aprilia, Yesi (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study aims to develop an electronic module based on Problem Based Learning (PBL) to improve the life skills of fifth-grade Madrasah Ibtidaiyah students. This study uses the Research and Development (R&D) method with 34 students from MIN 1 and MIN 4 Pringsewu as subjects. The research model developed uses ADDIE (Analysis, Design, Development, Implementation, and Evaluation). Data collection was conducted through observation, questionnaires, and documentation. Data analysis was performed to determine the product's score or validity based on expert validation from media experts, language experts, and subject matter experts, as well as student responses using a Likert scale. The research results showed that based on subject matter expert validation, the module achieved a percentage of 96.67%, media expert validation achieved a percentage of 92%, and language expert validation achieved a percentage of 84.67%. Thus, based on the validation of these three experts, the electronic module was categorised as ‘Highly Feasible.’ In the small-scale trial, the average percentage was 90.57%, while in the large-scale trial, the percentage achieved increased to 90.83%, so the electronic module was categorised as ‘Very Interesting’.